DETERMINANTS OF CONTRACEPTIVE USE AND FERTILITY AMONG REPRODUCTIVE-AGE COUPLES IN MANGGIS DISTRICT - Komang Tri Cahayani Febriyanti; Anak Agung Istri Ngurah Marhaeni (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the determinants of contraceptive use and fertility among PUS in Manggis District, Karangasem Regency. The variables examined include household income, women's education level, child gender preference, and healthcare access as exogenous variables; contraceptive use as a mediating variable; and fertility as the endogenous variable. This research employs a quantitative approach with an associative design. A sample of 60 respondents was selected using quota sampling combined with accidental and snowball sampling techniques. Data were collected through questionnaires, structured and in-depth interviews, and observation, and analyzed using descriptive statistics and path analysis. The results reveal that household income, women's education level, and healthcare access have a positive effect on contraceptive use, meanwhile PUS who have a child gender preference have a shorter duration of contraceptive use. Furthermore, household income, women's education, healthcare access, and contraceptive use negatively affect fertility, whereas PUS who have a preference for the sex of the child have a higher fertility rate. Contraceptive use is also proven to partially mediate the effect of all exogenous variables on fertility.